Efficiency Analysis of LICI and Select Private Sector Life Insurance Companies in India - A Comparative Study - Iffat Jahan Qaiser, (Management Journal for Advanced Research, 2022)
Insurance refers as a contract in which the insured transfers risk of potential loss to the insurer who promises to compensate the former upon suffering loss. The promise is called the insurer and the promise is called the insured. Insurance premium is the monetary consideration paid by the insured to the insurer for the cover granted by the insurance policy. The objective of the present study is to investigate the factors affecting efficiency of insurance companies operating in India. The target population of the study was 24 public and private life insurance companies and four important financial ratios. For which 10 years audited financial statements of the companies from 2009 to 2019 was studied for analysis. The secondary data were collected by reviewing of financial statements and related published and unpublished materials to achieve the objective of this study.